How External Environment and Altruistic Traits Drive Eco-Centric Entrepreneurial Intention Among Youth in the Post-COVID-19 Era? - Weng, Yudong; Pasha, Ahmad Tisman; Malik, Muhammad Shaukat; Farooq, Muhammad Umar; Hussain, Siraj (Frontiers in Psychology, 2022)
Green entrepreneurship is a recent business phenomenon that can seek out the ecological issue. In the time of COVID19, every business entity is looking forward to the unique way to be more resilient and noticeable. In this regard, green entrepreneurs hold the potential to manage scarce resources, fulfill social responsibility, and put forward the solution to environmental degradation in the new normal of the post-COVID19 era. The current venture investigates the opportunity recognition and the readiness behavior to execute the green entrepreneurship intentions during the post-COVID-19 situation (specifically by underlining the role of market orientation. The present model has examined the institutional theory. It has put forward the opportunity recognition behavior in the post-COVID19 era, which can improve youth readiness to opt for green entrepreneurship. The study collected the data from the 196 university graduate students from the university students via online sources by using purposive sampling. The study has found that the proposed hypothesis has been proved significant while defining the green entrepreneurial intentions. Particularly the study has shown that warm glow has contributed as the strongest factor to predict the Green entrepreneur intention. Moreover, the contributes by employing the institutional theory as a novel aspect in the academic sphere.